2017
DOI: 10.1002/solr.201700129
|View full text |Cite
|
Sign up to set email alerts
|

Instability of Increased Contact Resistance in Silicon Solar Cells Following Post‐Firing Thermal Processes

Abstract: Recently, there have been reports of increased series resistance as a consequence of thermal processes applied after the co‐firing of screen‐printed silicon solar cells. A previous observation of this effect on very heavily diffused emitters concluded that the increased series resistance is the result of a thickening of the glass layer surrounding silver crystallites at the Ag‐Si interface. Here, large increases in the front silver contact resistance after particular thermal anneals are reported that have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 16 publications
6
21
0
Order By: Relevance
“…It has been suggested that this unstable increase in contact resistance is related to the motion of hydrogen [10]. This is in good agreement with recent simulations on the re-distribution of hydrogen at similar temperatures [11] which predicts that there will be a significant build-up of hydrogen at the metal contacts.…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations
“…It has been suggested that this unstable increase in contact resistance is related to the motion of hydrogen [10]. This is in good agreement with recent simulations on the re-distribution of hydrogen at similar temperatures [11] which predicts that there will be a significant build-up of hydrogen at the metal contacts.…”
Section: Introductionsupporting
confidence: 89%
“…These processes are often intended to getter or improve passivation of defects [1][2][3][4], or to mitigate degradation effects [5][6][7][8]. While these approaches have proven to be effective in improving the bulk lifetime and longterm stability of devices, an unintended consequence has been a reported increase in device series resistance (RS) [5,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the hydrogenation appeared to be having another impact on the FF, actually causing it to be worse on the standard cells (72.4), or those with less significant anchor point damage (50% coverage or less). It is well‐known that hydrogen can passivate or neutralize dopants in the bulk or emitter regions, and more recently, it has also been suggested that hydrogen could play a role in increasing front contact resistance on screen print contact cells, which could potentially also occur in the case of plated contacts . It is therefore possible that hydrogenation processes can increase the series resistance of a cell, which could potentially cause the observed FF loss.…”
Section: Discussionmentioning
confidence: 99%